2022
DOI: 10.3390/microorganisms10112246
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in Various Parts of Air-Conditioning Units in 17 Japanese Houses

Abstract: HVAC systems have a significant impact on the indoor environment, and microbial contamination in HVAC systems has a significant effect on the indoor air quality. In this study, to gain a better understanding of the microbial contamination inside ACs, we used NGS to analyze the 16S rRNA gene of bacteria adhering to AC filters, cooling coils, fans, and air outlet surfaces. The five phyla in terms of the highest relative abundance were Proteobacteria, Firmicutes, Actinobacteria, Cyanobacteria, and Bacteroidetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In a study by Watanabe et al, Bacillus sp. was one genus of bacteria shown to frequently exist in the air in Japanese residential areas [ 57 ]. This allows Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Watanabe et al, Bacillus sp. was one genus of bacteria shown to frequently exist in the air in Japanese residential areas [ 57 ]. This allows Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial communities inhabiting automobile air conditioning (AC) systems have garnered increasing attention due to their potential impact on indoor air quality, human health, and the performance of AC systems [1,2]. These microbial communities thrive in the moist and nutrient-rich environments provided by AC systems, which can serve as ideal habitats for their growth and proliferation [3]. Understanding the composition, diversity, and dynamics of microbial communities in these environments is crucial for mitigating the potential health risks associated with indoor air contamination and ensuring the efficient operation of AC systems.…”
Section: Introductionmentioning
confidence: 99%
“…The heating, ventilation, and air-conditioning (HVAC) filters could be a viable option for estimating indoor biological contaminants [ 24 ]. The HVAC systems significantly impact the indoor environment, and HVAC systems contaminated by microorganisms can cause severe indoor air quality problems [ 25 ]. Low indoor air quality can harm human health because people tend to spend more than 80% of their time in the indoor environment, suggesting that it is urgent to understand the microbiota in case of unexpected health risks caused by microbial contamination [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary research mainly focuses on bacteria and fungi [ 28 ]. Most research revealed that the microbial community structure in HVAC systems was dominated by Proteobacteria, Actinobacteria, Firmicutes, Cyanobacteria, and others [ 25 ]. Cyanobacteria were usually detected, and occupied a proportion, but lacked further systematic analysis.…”
Section: Introductionmentioning
confidence: 99%